Biocontrol Potential of Microfighter: A Zeolite-Based Product Enriched with Pseudomonas synxantha DSL65 - Elena Cudazzo; Lucia Morrone; Giacomo Ferretti; Barbara Faccini; Daniele Mirandola; Luca Fagioli; Annalisa Rotondi (Agronomy, 2025)
Particle film technology is an environmentally sustainable crop protection method, offering an alternative to chemical pesticides for disease control. Copper-based compounds have long been central to the management of bacterial and fungal diseases, particularly in organic agriculture. However, due to their environmental persistence, their use has been increasingly restricted by European regulations, making the management of widespread diseases such as Olive Knot (Pseudomonas savastanoi pv. savastanoi) and Downy Mildew (Plasmopara viticola) more difficult. The LIFE Microfighter project addresses this problem by testing a novel Zeo-Biopesticide (ZBp), in which natural zeolite serves as a carrier for the beneficial bacterium Pseudomonas synxantha DLS65. Field trials conducted in high-rainfall areas of Emilia-Romagna (Italy) evaluated the product’s distribution and persistence on olive and grape leaves through ESEM (Environmental Scanning Electron Microscopy) observations, its ability to retain the microorganism, and its effectiveness for disease control. Results showed that ZBp significantly reduced Olive Knot incidence compared to both the untreated control and Cu-based treatments (p < 0.05), supporting its potential as an alternative for bacterial disease management, while showing no statistically significant difference compared to the control in either the incidence or severity of Downy Mildew (p > 0.05). Its persistence and adherence to plant surfaces, which could influence its overall field performance, were affected by environmental conditions, particularly rainfall.